Relationships between Regional Radiation Doses and Cognitive Decline in Children Treated with Cranio-Spinal Irradiation for Posterior Fossa Tumors - Doger de Speville, Elodie; Robert, Charlotte; Perez-Guevara, Martin; Grigis, Antoine; Bolle, Stephanie; Pinaud, Clemence; Dufour, Christelle; Beaudré, Anne; Kieffer, Virginie; Longaud, Audrey; Grill, Jacques; Valteau-Couanet, Dominique; et al. (Frontiers in Oncology, 2017)
Pediatric posterior fossa tumors (PFT) survivors who have been treated with cranial radiation therapy often suffer from cognitive impairments that might relate to IQ decline. Radiotherapy distinctly affects brain regions involved in different cognitive functions. However, the relative contribution of regional irradiation on the different cognitive impairments still remains unclear. We investigated, in thirty children treated for a PFT, the relationships between the changes in different cognitive scores and radiation dose distribution. We aimed to designate areas of the brain that should be preferentially avoided, whenever possible. Our exploratory analysis was based on a Principal Component Analysis and an Ordinary Least Square regression approach. The use of a Principal Component Analysis was an innovative way to cluster correlated irradiated regions due to similar radiation therapy protocols across patients. Our results suggest an association between working memory decline and high dose (Equivalent Uniform Dose, EUD) delivered to the orbitofrontal regions; whereas decline of processing speed seemed more related to EUD in the temporal lobes and posterior fossa. To identify regional effects of radiotherapy on cognitive functions may help to propose a rehabilitation program adapted to the risk of cognitive impairment.